Complexities of Conflict: Climate Change, Elephants and Local Livelihoods in Lupane, Zimbabwe - Ndlovu Joram; Douglas Nyathi (E-Journal of Humanities, Arts and Social Sciences)
The conflict between humans and wildlife can result in negative impacts on both parties and hinder conservation efforts. By predicting how conflict risks may change with a growing agricultural sector and human population under a changing climate, policymakers can effectively allocate resources for mitigating and conserving conflict-prone species and regions. This study investigated the drivers of human-elephant conflict in Lupane, Zimbabwe, emphasizing the role of climate change and variability. Using an ethnographic approach informed by the sustainable livelihoods framework and political ecology, it examined how changing climatic conditions, such as water shortages, rising temperatures, and diminishing grazing, exacerbate conflicts between humans and elephants. These challenges have led to increased human intrusion into elephant territories, driven by collapsing rain-fed agriculture and a need for diversification into forestry-based livelihoods. The consequences of this conflict have been severe, resulting in injuries, deaths, damage to crops and infrastructure, economic losses, and food insecurity for affected households. As human populations grow and the impacts of climate change become more pronounced, the risk and geographical spread of human-elephant conflict are expected to escalate. The study highlights the importance of understanding these dynamics to inform policymakers in resource allocation for conflict mitigation and conservation efforts. It also critiques existing institutional support systems for addressing human-elephant conflict, assessing their climate sensitivity. To enhance sustainability, the research advocates for integrating empirical data on human-wildlife coexistence into international conservation policies and developing comprehensive, long-term strategies at a transboundary level, particularly in the context of climate change.